THE INFLUENCE OF AL-FARABI'S PHILOSOPHY OF EDUCATION ON THE DEVELOPMENT OF TEACHING METHODS OF ISLAMIC RELIGIOUS EDUCATION - M. Thuba, M. Thuba; Said, Basnang (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to examine the influence of Al-Farabi’s educational philosophy on the development of teaching methods in Islamic religious education and to formulate an actionable pedagogical model based on his thought. Employing a qualitative library-research methodology, this investigation critically reviews primary and secondary sources pertaining to Al-Farabi’s educational philosophy and its relevance within a contemporary Islamic educational context. The findings reveal that Al-Farabi’s core principles namely the integration of reason and revelation, the concept of felicity (al-saʿādah), and the vision of the virtuous city (al-madīnah al-faḍīlah) provide a robust foundation for designing an integrated curriculum, positioning the teacher as a philosophical mediator, and cultivating a learning environment conducive to the formation of the insān kāmil (perfect human) and a civilized society. This study further proposes a novel theoretical framework entitled Falsafiyyah Tarbawiyyah, structured around three pillars: Taʿlīm al-Maʿqūl wa al-Manqūl (rational-textual instruction), Taḥzīb al-ʿAql wa al-Qalb (purification of intellect and heart), and Takwīn al-Mujtamaʿ al-Faḍīl (formation of an exemplary society). In conclusion, Al-Farabi’s educational philosophy proves not only theoretically pertinent but also practically applicable in developing holistic and transformative teaching methods for Islamic religious education, thereby addressing the challenges of modern Islamic pedagogy. The proposed model opens avenues for more innovative and contextually relevant educational practices.